Lessons from rheumatoid arthritis and inflammatory bowel disease: The importance of patient-centred outcomes in severe asthma - Joseph W. Lanario; Matthew Masoli; Michael E. Hyland (Exploration of Asthma & Allergy, 2026)
Biologic therapies have transformed care for people with severe asthma, yet treatment response has traditionally been assessed using clinician-derived measures, including lung function, exacerbation rates, and oral corticosteroid use. These metrics, while clinically important, frequently fail to capture what matters most to patients: their ability to participate in daily life, maintain relationships, and sustain work and social roles. The publication of the Core Outcome Measures Set for Severe Asthma (COMSA) and the subsequent CompOsite iNdexes For Response in asthMa (CONFiRM) composite score mark a shift towards patient-centred measurement of treatment response in severe asthma. Rheumatoid arthritis (RA) and inflammatory bowel disease (IBD) travelled this path decades earlier. Both conditions adopted composite scoring tools, such as the Disease Activity Score-28 (DAS28) and the Mayo Score, that incorporated Patient-Reported Outcome Measures (PROMs) alongside objective markers. Initiatives like Outcome Measures in Rheumatology (OMERACT) in RA and Selecting Therapeutic Targets in Inflammatory Bowel Disease (STRIDE) in IBD demonstrate that sustained, multidisciplinary collaboration between patients, clinicians, regulators, and industry can successfully embed PROMs into clinical trials and routine care. We argue that timely integration of health-related quality of life measures into clinical trials and practice requires electronic data collection, regulatory endorsement of PROMs as co-primary endpoints, and genuine patient partnership in research, beyond tokenism. By learning from parallel specialties, the asthma community can build a model of care that reflects what truly matters to those living with the disease.